The diet of the Weddell Seal Leptonychotes weddellii at the Danco Coast, 4 Antarctic Peninsula - Casaux, Ricardo Jorge; Baroni, A.; Ramón, A. (Polar Biology)
The diet of the Weddell Seal Leptonychotes weddellii at the Danco Coast, Antarctic Peninsula, was investigated by the analysis of 105 and 39 faeces col- lected at beaches surrounding Cierva Point during Jan- uary–March 1998 and 2000, respectively. The diet was diverse and composed of both pelagic and benthic- demersal organisms. Fish, followed by cephalopods, constituted the bulk of the diet by number and mass. Among fish, Pleuragramma antarcticum , Chaenodraco wilsoni and Gobionotothen gibberifrons were the domi- nant fish by mass in 1998, whereas Chionodraco ra- strospinosus , P. antarcticum and C. wilsoni predominated by mass in 2000. The contribution of channichthyid species to the diet of seals at the Danco Coast was higher than previously reported. Besides those species, the myctophid Electrona antarctica was also an important prey by number in the diet of seals in both summer seasons. The results are compared with information from other study areas and the possibility of using information on the diet of this seal as a gross indicator of fish availability/distribution is considered. Fil: Casaux, Ricardo Jorge. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. LIESA. Laboratorio de Investigaciones en Ecología y Sistemática Animal; Argentina Fil: Baroni, A. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Ramón, A. Universidad Nacional de La Plata; Argentina